PERAN PENGEMBANGAN EKONOMI KREATIF IKAN SALAI DALAM UPAYA PENCIPTAAN LAPANGAN KERJA DAN PENINGKATAN KESEJAHTERAAN MASYARAKAT - Arman Syafii Harahap; Marliyah Marliyah; Budi Dharma (JURNAL ILMIAH EDUNOMIKA, 2024)
The creative economy is an economic movement managed by local communities where the main processed products of the creative economy come from natural resources, for example in the culinary world which provides its own challenges for Padang Lawas Regency, namely how to promote and develop smoked fish culinary amidst the rise of modern culinary, in efforts to create new jobs and achieve community welfare. The aim of this research is to analyze and determine the role of the creative economy in Huristak District, Barumun Tengah District, Aek Nabara Barumun District, especially in the local smoked fish culinary sector, Padang Lawas Regency, North Sumatra. This type of research is qualitative research which is analyzed using descriptive methods. The data collection technique used in the research was collected from data from the 2021 Central Statistics Agency (BPS) of Padang Lawas Regency and collected from observation data, in-depth interviews, literature studies and documentation, then a data analysis technique developed by Miles, Huberman and Saldana was carried out using four flow of activities in data analysis, namely, data collection, data condensation, data presentation, and drawing conclusions. The research results found that the creative economic role of smoked fish in Padang Lawas Regency can improve the economic welfare of the community and efforts to create jobs.